PROFESSIONAL LIABILITY INSURANCE OF MEDICAL PROFESSIONALS AS A MECHANISM FOR PROTECTING THE RIGHT TO HEALTH PROTECTION - Tlembayeva Жанна Урумбасаровна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2025)
The article examines the legal basis for professional liability insurance of medical professionals as an effective mechanism for protecting the right to health protection. The author focuses on the specifics of medical activities associated with the risks of harm to patients’ health, which can be caused not only by professional violations, but also by other subjective and objective factors (for example, poorly understood diseases, poor material equipment of clinics, etc.). A review of professional liability insurance systems for medical professionals in developed foreign countries is conducted. An analysis of the best practices of medical personnel insurance in various countries shows that despite differences in approaches to regulation, it is aimed at protecting doctors from financial risks and ensuring guaranteed compensation for harm caused to the health or life of patients. The article analyzes the conditions for professional liability insurance for harm caused in the provision of medical services, the features of the professional liability co-insurance agreement for medical professionals, and its content. The author’s definitions of terms related to professional liability insurance for medical workers are given. Particular attention is paid to the characteristics of the insurance object, the insurance event, which are considered in the context of the objectives of professional liability insurance. Based on the analysis of domestic and foreign insurance systems, the author identifies the main advantages and opportunities for professional liability insurance of medical professionals in Kazakhstan. It is concluded that the insurance rules established by law (mandatory nature of insurance, establishment of the amount of insurance premiums and insurance payments, the presence of an independent body for reviewing patient complaints about compensation) are aimed at ensuring fairness and transparency of insurance procedures. The problems of legislation and practice of applying the new type of insurance are identified, and ways to solve them are proposed.